A Parade or a Riot: A Discourse Analysis of Two Ethnic Newspapers on the 2011 Marching Season in Northern Ireland - Ferman, Dave (Journal of media and religion, 2013)
The annual marching season in Northern Ireland has long been the site of ethnic/religious controversy and violence pitting Catholics against Protestants. This study analyzes how more than 80 news stories from two Belfast-based ethnic newspapers, the Catholic/nationalist Irish News and the Protestant/loyalist News Letter, framed the 2011 season. The research documents that the discourses and overarching themes presented by The Irish News and the News Letter were vastly different, with the former largely describing the season in negative terms and as the source of violence and civil unrest, and the latter portraying the season as a triumphant, and popular, display of loyalist culture.